Cyclization reactions of IMM-125 and oxidation of cyclosporin A amino-acid 1 in the α position of the double bond lead to the loss of in vitro immunosuppressive activity. Issue 4 (2000) - Dieden Dieden, R. R.; Latinne Latinne, D. D.; Baldari Baldari, C. C.; Maton Maton, N. N.; Aubry Aubry, A. A.; Verbeeck Verbeeck, R. K. R. K.; Zurini Zurini, M. M.; Lhoëst Lhoëst, G. J. J. G. J. J.
Abstract : Cyclosporin A (CsA) and IMM-125, a hydroxyethyl derivative of D-serine CsA, are cyclic undecapeptides of molecular weight 1201.8 and 1261.8, respectively. The main metabolites still possessing the undecapeptide structure were found to be compounds resulting from the biotransformation of amino acids 4, 9 and 1. Under the influence of the hepatic cytochrome P-450-dependent monooxygenase system, CsA and IMM-125 amino acid 1 are metabolized to a mono-hydroxylated compound (metabolite M-17) and to a dihydrodiol. A metabolite M18 was found to be the result of a non-enzymic intramolecular formation of a tetrahydrofuran derivative from metabolite M17. Since the existence of a CsA dihydrodiol was reported and since epoxides are considered as the dihydrodiol precursors, the aim of the present work was to prove that the same non-enzymic intramolecular formation of a tetrahydrofuran ring could occur by nucleophilic attack of the amino-acid 1 β -hydroxy group at the ɛ -position of the freshly formed epoxide by reaction of IMM-125 with m-chloro-perbenzoic acid and cyclosporin A with selenium oxide. The immunosuppressive activity of the compounds, as measured by the mixed lymphocyte reaction and by the luciferase activity of a Jurkat-T-cell line stably transfected with the NF-AT/luc reporter plasmid, was found negligible for IMM-125 compared to the parent drug as well as for the cyclosporin A derivative. Structures of the IMM-125 and CsA derivatives were elucidated by electrospray mass‒spectrometry and NMR spectroscopy.